Identifying patient‐important outcomes in polycystic kidney disease: An international nominal group technique study. Issue 12 (2nd May 2019) - Cho, Yeoungjee; Sautenet, Benedicte; Gutman, Talia; Rangan, Gopala; Craig, Jonathan C; Ong, Albert C; Chapman, Arlene; Ahn, Curie; Coolican, Helen; Kao, Juliana T‐W; Gansevoort, Ron; Perrone, Ronald D; et al.
ABSTRACT: Aim: Patients with autosomal dominant polycystic kidney disease (ADPKD) are at increased risk of premature mortality, morbidities and complications, which severely impair quality of life. However, patient‐centered outcomes are not consistently reported in trials in ADPKD, which can limit shared decision‐making. We aimed to identify outcomes important to patients and caregivers and the reasons for their priorities. Methods: Nominal group technique was adopted involving patients with ADPKD and caregivers who were purposively selected from eight centres across Australia, France and the Republic of Korea. Participants identified, ranked and discussed outcomes for trials in ADPKD. We calculated an importance score (0–1) for each outcome and conducted thematic analyses. Results: Across 17 groups, 154 participants (121 patients, 33 caregivers) aged 19 to 78 (mean 54.5 years) identified 55 outcomes. The 10 highest ranked outcomes were: kidney function (importance score 0.36), end‐stage kidney disease (0.32), survival (0.21), cyst size/growth (0.20), cyst pain/bleeding (0.18), blood pressure (0.17), ability to work (0.16), cerebral aneurysm/stroke (0.14), mobility/physical function (0.12), and fatigue (0.12). Three themes were identified: threatening semblance of normality, inability to control and making sense of diverse risks. Conclusion: For patients with ADPKD and their caregivers, kidney function, delayed progression to end‐stage kidney disease and survival were the highest priorities, and were focused on achieving normality, and maintaining control over health and lifestyle. Implementing these patient‐important outcomes may improve the meaning and relevance of trials to inform clinical care in ADPKD. SUMMARY AT A GLANCE: The authors identified and ranked 55 patient‐centered outcomes in 121 autosomal dominant polycystic kidney disease patients and 33 of their caregivers from 17 groups from Australia, France and Korea. They found kidney function, delayed progression to end‐stage kidney disease and survival to be of the highest priorities. These data could help to design clinical trials in autosomal dominant polycystic kidney disease and health education.